Understanding the family Involvement in caring older people with chronic musculoskeletal pain in the community - Mohd Jaias, Nurin Syafiqah; Firdaus, Mohd Khairul Zul Hasymi; Nik Mohd Hatta, Nik Noor Kaussar; Mat, Sumaiyah; Arifin, Hidayat; Che Hasan, Muhammad Kamil (Universiti Putra Malaysia, 2025)
Introduction: Worldwide, the family unit serves as the main social framework, and older people predominantly depend on their relatives for healthcare and support. However, there are other facets of issues related to the strain of caregiving. This study aimed to investigate the health beliefs, experiences, expectations, cultural and religious beliefs of family members of older people with chronic musculoskeletal pain in managing symptoms and supporting older people in the community.